Current gain controlled CFTA and Its application to resistorless quadrature oscillator - Prasertsom, Danucha; Tangsrirat, Worapong (My University, 2012)
This paper presents the concept of the current follower transconductance amplifier (CFTA) with current gain controllable. The newly modified element is a combination of the current follower, the variable gain current mirror, and the balance output transconductance amplifier. The advantage of the proposed element is that the current transfer characteristics (i z/i f and i x/i z) can be electronically tuned by means of external bias currents. As application example, the resistorless realization of current-mode quadrature oscillator based on the proposed current controlled gain CFTA element is also presented. PSPICE simulation results of the proposed circuit and its application are given to confirm the theoretical analysis. © 2012 IEEE.
Keywords: Current Follower Transconductance Amplifier (CFTA); current-mode circuit; Quadrature Oscillator (QO); resistorless realization